Respostas
respondido por:
1
m(3): (51....147)
a1 = 51
an = 147
r = 3
n = ?
an = a1 + (n - 1).r
147 = 51 + (n - 1).3
147 - 51 = 3n - 3
96 = 3n - 3
96 + 3 = 3n
99 = 3n
3n = 99
n = 99/3
n = 33
Sn = (a1 + an).n
2
Sn = (51 + 147).33
2
Sn = 198.33
2
Sn = 99.33
Sn = 3267
a1 = 51
an = 147
r = 3
n = ?
an = a1 + (n - 1).r
147 = 51 + (n - 1).3
147 - 51 = 3n - 3
96 = 3n - 3
96 + 3 = 3n
99 = 3n
3n = 99
n = 99/3
n = 33
Sn = (a1 + an).n
2
Sn = (51 + 147).33
2
Sn = 198.33
2
Sn = 99.33
Sn = 3267
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás